Answer:
Step-by-step explanation:
It can’t be determined because there is too many numbers
Answer:
ln [(x + 2)^3 ]/(x-1)
Step-by-step explanation:
3ln(x+2) - ln(x - 1) = ln (x + 2)^3 - ln (x-1)
ln (x + 2)^3 - ln (x-1) = ln [(x + 2)^3 ]/(x-1)
The answers to the question is -33
(f×g)(-1) is -14.
Step-by-step explanation:
- Step 1: Calculate (f×g)(x) by using the formula (f×g)(x) = f(x) × g(x)
⇒ (f×g)(x) = (x + 3)(4x - 3)
⇒ (f×g)(x) = 4x² - 3x + 12x - 9
⇒ (f×g)(x) = 4x² + 9x - 9
- Step 2: Find (f×g)(-1) by substituting -1 in the place of x
⇒ (f×g)(-1) = 4(-1)² + 9(-1) - 9
⇒ (f×g)(-1) = 4 - 9 - 9 =-14